Gestão de custos agropecuários sob o enfoque da análise do fluxo de caixa - Caiki Calepso Fantini (2023)
The objective of this thesis was to evaluate the current scenario of beef cattle, market aspects and the management of agricultural costs as a tool in the face of adversity under the focus of cash flow analysis and technical-economic indicators. After surveying the cost management methodologies and the main indicators, they were applied in a property located in the municipality of Bodoquena – Mato Grosso do Sul (MS), with a “complete cycle” type creation system, in the period from July 2015 to June 2020. For the analyses, a chart of accounts was constructed, and the ABC cost curve methodology was adopted. The recorded inflows and outflows were classified according to the chart of accounts and presented through cash flow and the income statement for the year (DRE). Another management tool used were the technical-economic indicators: stocking rate, arrobas (unit equivalent to 15 kilograms) produced, revenues, total cost, and gross unit profit, measured per head, arrobas of carcass produced and per hectare. From the results it was possible to verify the composition of property costs, in addition to the level of importance that they exert on the activity, being the effective operating costs in order of relevance, nutritional inputs, labor, energy and fuels, maintenance, pasture, reproductive and sanitary inputs. Based on the cash flow, it was observed that the property obtained positive flow in all production cycles, being able to bear the investments, the total costs and still generate an accumulated final balance of R$3,521,873. Through the DRE, variations in gross profit were observed, with the lowest value recorded in the 2018/19 harvest (R$211,453), and the highest in the 2019/20 harvest (R$1,936,398). The lower profit values found were due to the increasing increase in costs and the significant reduction in the volume slaughtered. The recovery in the following season was due to the recovery in production volume and the inflationary effects. The form of financial calculation through the agricultural year (July to June) was evaluated in comparison to the calendar year (January to December) in order to identify the best methodology. In comparison, the values were very discrepant between the analyzes, including by viewing by calendar year there was a period of loss not previously identified. Allied to this, it was not possible to identify the criterion of seasonality in the production and marketing of animals, a basic premise to justify the use of the agricultural year.